链传动运动特性的模拟 - 李玉平; 周里群; 张高峰 (Jixie chuandong)
The stereogram effect of chain transmission was simulated by 3DS MAX, the bounce effect of chain and inhomogeneity of chain velocity was shown directly in picture.